2010
DOI: 10.1038/ijo.2010.196
|View full text |Cite
|
Sign up to set email alerts
|

Vaspin is related to gender, puberty and deteriorating insulin sensitivity in children

Abstract: Background: Visceral adipose tissue-derived serine protease inhibitor (vaspin) has been suggested as a novel adipocytokine related to obesity and insulin sensitivity in adults. Design: We quantified vaspin serum concentrations in 65 lean and 67 obese children and aimed to evaluate the relationship of vaspin with physical development, obesity, and metabolic and cardiovascular phenotypes in children. We further assessed the acute vaspin response to glucose provocation in 20 obese adolescents and evaluated tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
4
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 23 publications
7
57
4
9
Order By: Relevance
“…The recently published data is parallel with our data by means that vaspin plays an important role in childhood obesity. Our results, however, contradict those of previous studies showing that elevated vaspin concentrations are not related to obesity [13,21]. This discrepancy may be partly explained by different population origins of study sub- 001 Independent variables were included in multiple linear regression analysis if p value was less than 0.10 in univariate linear regression analysis.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…The recently published data is parallel with our data by means that vaspin plays an important role in childhood obesity. Our results, however, contradict those of previous studies showing that elevated vaspin concentrations are not related to obesity [13,21]. This discrepancy may be partly explained by different population origins of study sub- 001 Independent variables were included in multiple linear regression analysis if p value was less than 0.10 in univariate linear regression analysis.…”
Section: Discussioncontrasting
confidence: 97%
“…However, these previous studies also included relatively small numbers of participants with a wide age range, resulting in small, heterogeneous study samples [13,21]. The present study had a larger sample size and all children were the same age.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The body fat percentage was found to be the strongest predictor of visceral vaspin, and insulin sensitivity seems to be the strongest determinant of subcutaneous vaspin expression [17]. On the other hand, Körner et al [19] revealed that vaspin concentration was lower in obese girls compared to lean controls; also, no correlation was found between serum vaspin and BMI. It is generally believed that differences in vaspin levels between obese individuals (children, adolescents, adults) are related to gender, age, physical activity, and hormone metabolism.…”
Section: Introductionmentioning
confidence: 95%